CAPITAL STRUCTURE ANALYSIS IN MINING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Sulistianingsi, Nilla; Nofal, Mohammad; Hatma, Ramli (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to analyze the capital structure of mining companies listed on the Indonesia Stock Exchange by examining 4 fundamental factors, namely Asset Structure, Profitability, Sales Growth and Company Size. The research sample was 41 mining companies on the Indonesia Stock Exchange in 2016-2020. For the panel data regression analysis technique, Software Econometric Views (Eviews) version 12 was used. Based on the results of the analysis, the direct influence is concluded that 1) Asset Structure, Profitability, Sales Growth and Company Size simultaneously have a positive and significant effect on the company's capital structure Mining on the Indonesia Stock Exchange for the period 2016-2020; 2) Asset structure has no significant positive influence on capital structure; 3) Profitability has a negative and significant effect on capital structure; 4) Sales growth has a negative and insignificant influence on capital structure; and 5) Company size has a negative and significant effect on the capital structure of mining companies listed on the Indonesia Stock Exchange in 2016-2020. Keywords: Capital Structure, Asset Structure, Profitability, Sales Growth and Company Size